Numerical investigation of natural convection in concentric cylinder partially heated based on MRT-lattice Boltzmann method. (March 2022) - Farkach, Younes; Derfoufi, Soufiane; Ahachad, Mohammed; Bahraoui, Fatima; Mahdaoui, Mustapha
Abstract: In the present paper, a numerical simulation of natural convection flow in annulus space with a partially heated inner cylinder is proposed. The numerical investigation is based on lattice Boltzmann method (LBM) with multiple relaxation time approximation. Each heating partial side length's is about 25% of the inner perimeter and is maintained at hot temperature. The heated regions are placed on the inner wall in four different configurations while the outer cylinder is maintained at cold temperature. A study of effect of Rayleigh number varying over the range of 10 4 - 5 × 10 5 and various cylinder ratio on Nusselt number and both velocity and thermal fields is carried out. It is found that the Nusselt number increases with the increase of Rayleigh number and the radius ratio. Otherwise, the fourth configuration where the heated zones are placed on the left and right sides of the inner cylinder, offers the better rate heat exchange for a fixed value of Rayleigh number and radius ratio.